2011
DOI: 10.1002/mds.23814
|View full text |Cite
|
Sign up to set email alerts
|

The relation between cognition and motor dysfunction in drug‐naive newly diagnosed patients with Parkinson's disease

Abstract: Recent studies have reported cognitive decline to be common in the early phase of Parkinson's disease. Imaging data connect working memory and executive functioning to the dopamine system. It has also been suggested that bradykinesia is the clinical manifestation most closely related to the nigrostriatal lesion. Exploring the relationship between motor dysfunction and cognition can help us find shared or overlapping systems serving different functions. This relationship has been sparsely investigated in popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 30 publications
9
107
2
4
Order By: Relevance
“…Some investigators include speech and facial expression (bulbar features) or neck rigidity as additional axial motor items [25][26][27]. In our study, LBD subjects, while matched for UPDRS III total score, did significantly worse than the PD subjects on only PIGD items (Table 2).…”
Section: Differentiation Of Pd and Lbd Subjects Based On Motor Characmentioning
confidence: 48%
See 3 more Smart Citations
“…Some investigators include speech and facial expression (bulbar features) or neck rigidity as additional axial motor items [25][26][27]. In our study, LBD subjects, while matched for UPDRS III total score, did significantly worse than the PD subjects on only PIGD items (Table 2).…”
Section: Differentiation Of Pd and Lbd Subjects Based On Motor Characmentioning
confidence: 48%
“…The pattern of cognitive deficits in PDD and DLB, however, appears to differ in significant ways from that of AD [4-7, 9, 10, 23]. Furthermore, evidence suggests that there are specific relationships between motor and gait impairment patterns and the type of cognitive impairment or dementia condition present [1,2,[24][25][26][27][28][29][30].…”
Section: Dw Scharre Et Al / Comparing Lbd With Ad and Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…In early stages of PD, bradykinesia has been correlated with working memory and executive functioning, whereas rigidity and tremor were not correlated with any cognitive measures (Domellof et al 2011). Fleischman et al (2005 found no specific relationship between MPS and cognitive performance in a cohort of older adults without PD.…”
Section: Discussionmentioning
confidence: 99%